Identifikasi Kandungan Hidrokuinon Dalam Krim Pemutih Wajah yang Beredar di Pasar Kodim Pekanbaru Dengan Metode Kromatografi Lapis Tipis (KLT) - vonny kurnia utama; Putri Hananda (LPPM Universitas Abdurrab, 2023)
Facial whitening cream is included in cosmetic preparations that are used to beautify oneself. Hydroquinone is a hazardous substance which is prohibited for use in cosmetic preparations. Based on BPOM regulations, hydroquinone is included in the class of hard drugs and must be used with a doctor's prescription. The purpose of this study was to determine whether or not hydroquinone was present in face whitening creams sold at the Pekanbaru Kodim Market using the Thin Layer Chromatography method, with the principle of Thin Layer Chromatography, namely the improvement of multi-component compounds using two phases, namely the stationary phase and the mobile phase. The stationary phase used was silica gel GF 254 nm and the mobile phase used was toluene and glacial acetic acid (8:2). From the results of this test, the standard Rf value of hydroquinone was 0.41 with the Rf value of sample 1, which was 0.42, the Rf value of sample 2, which was 0.43, the Rf value of sample 3, which was 0.40 and the Rf value of sample 4, which was 0.41. these results show that even the standard hydroquinone Rf value is the same or almost the same as the sample solution value of not more than 0.05. From this test, it was concluded that even all the samples tested tested positive for hydroquinone, which was indicated by the presence of purple blotches parallel to the sample tested with the hydroquinone standard, and the Rf value of the sample and standard obtained was not more than 0.05.